The effects of number of natural teeth and number of posterior occluding pairs on the oral health-related quality of life in Thai elderly patients at Faculty of Dentistry, Chulalongkorn University - Kwanrutai Somsak (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012